The interaction of two dust particles in plasmas - Kravchenko, O.Yu.; Vakulenko, A.V. (Вопросы атомной науки и техники, 2009)
The process of charging and shielding of two dust particles is studied with a molecular dynamic method and Monte Carlo method for describing of elementary processes, such as elastic, excitation, ionization, charge exchange processes.The three-dimensional P3M molecular dynamics method [1] is applied as the most complete description of plasma particles motion and interaction with macroscopic dust grain. The interaction between plasma particles and neutral gas was simulated using MCC method. The two spherical conductive dust particles were located in nondisturbed low pressure low temperature plasma at different values of the neutral gas density. The spatial distribution of plasma particles around dust grains obtained at different interparticle distances. The formation of the common ion cloud and the effect of ion shadowing were observed at the decreasing of the interparticle distance. The dependence of the electrostatic and ion drag forces on the interparticle distance was investigated.